Massive Ascites in a Patient with Severe Preeclampsia - Alam, Irin Parveen (Sir Salimullah Medical College Journal, 2022)
Objective: To present a rare case of massive ascites with severe preeclampsia. Case Report: A 27-year-old, G2P1, woman presented at 37 weeks of gestation with severe preeclampsia with ascites with breech with intrauterine fetal growth restriction. A large amount of free fluid was noted intraperitoneally during caesarean section. Postoperatively ascites fluid continued to come through drain. Patient developed respiratory distress, hypertension and hypoproteinemia. Which were managed by multidisciplinary approach. These patients need intense surveillance to prevent complication. Sir Salimullah Med Coll J 2021; 29(2): 169-171